Iqbal's Philosophy of Humanitarianism and the contemporary world - Rabia Kayani (بازیافت, 2022)
"Iqbal's Philosophy of Humanitarianism and the contemporary world" Sir Allama Muhammad Iqbal was a bard, theorist, government official, and in addition a scholastic, lawyer and researcher in British India who is broadly viewed as having propelled the Pakistan Movement. He is known as the “Spiritual father of Pakistan”. He is viewed as one of the greatest significant figures in Urdu literature, with legendary effort in both the Urdu as well as Persian dialects. The humanitarian ideal is always universal in poetry and philosophy; but if you make it an effective ideal and work it out in actual life, you must start, not with poets and philosophers, but with a society exclusive, in the sense of having a creed and a well-defined outline, but ever enlarging its limits by example and persuasion. (Iqbal’s letter to Nicholson, in Hassan, The Sword and the Sceptre, p. 364.) He was born and brought up in the 20th century when the sun of the British Empire never set, and India was very much part of that Empire. Western imperialism was imposed on the east where our education, economy, politics, and society were overwhelmed by new ideology and beliefs. The society was overburdened with materialism as a result spiritualism had become a myth. In this environment Iqbal foster his philosophy. He in the history of world literature is the greatest poet of humanism. He has mentioned humanity in his poetry with so much love, care and affection, example of which is never found in the history. He was a great interpreter of humanism. Iqbal believed that to bring revolution in outer world it is necessary to transform inner world. At the outset one must be awakened then only there will be change in the world. Allama Iqbal developed his own philosophy after amalgamating the west with the east. He discussed the fundamental principles of Islam in the light of modern thought and scientific knowledge and made a searching analysis of its basis. Undoubtedly, he accepted divergent views expounded by the western philosophers and thinkers, but the soul of his philosophy lies in the Islam. He made a serious attempt at seizing the problems of modern western philosophy within an Islamic context. The idea behind Iqbal’s intellectual speculations was that the avaricious ideology of the West, coming down from nineteenth century observations of science, had failed mankind. Therefore, the spiritual philosophy of the East would come to the rescue of a divided humanity. According to Iqbal, the Industrial Revolution of the 18th century contaminated the West with excessive materialism and intoxicated with power, it lost its bearings and went berserk. Hence imperialism, both in the form of Capitalism and that of communism, corrupted America as well as Europe. The mantra of Democracy put forward by both is hollow and deceptive. The concept of aggressive nationalism ruined humanitarianism. Otherwise, human progress could go beyond the stars. Therefore, a redirection of thought and action was immediately required. The positive and productive process, Iqbal concluded, would get underway in the East, inspired by a total view of Islam, as a way of life for the entire mankind. He, in this endeavour, was inspired by western thinkers like Nietzsche and Muslim spiritual teachers like Mohammad Ibn al Arabi and Maulana Jalaluddin Rumi. Mohammad Ibn Arabi (1165-1240) was a great Aref (Gnostic) and expounder of Wahdat Alwojud. His famous statement, “It is He who is revealed in every face, sought in every sign, gazed upon by every eye, worshipped in every object of worship, and pursued in the unseen and the visible.